Fuzzy finite-time consensus control for uncertain nonlinear multi-agent systems with input delay - Yan, Yancheng; Li, Tieshan; Yang, Hanqing; Wang, Jianhui; Philip Chen, C.L. (Information sciences, 2023)
A fuzzy finite-time consensus control method for a class of uncertain nonlinear multi-agent systems (MASs) with input delay is developed. The Pade approximation approach and Laplace transform technology are employed to eliminate the effect of input delay. Then, the fuzzy logic systems are applied to deal with the uncertain nonlinear terms. Furthermore, a relative threshold event-triggered control scheme is established to alleviate the communication burden of the control network. Meanwhile, to ensure MASs can synchronize in finite time, an adaptive consensus control method is developed. With the proposed method, even if the MASs suffer from input delay, all followers in the MASs reach finite-time synchronization and track the virtual leader. Finally, the validity of the proposed method is illustrated by the theoretical analysis and simulation examples.